The complex analysis of the column station with depth variation - Petrenko, V. D.; Tiutkin, O. L.; Petrenko, V. I. (Science and Transport Progress, 2011)
In the article the results of complex analysis of the columnar station with variation of depth contour interval with research of mobile loading influencing on ceiling are represented.